Business park and industrial development handbook. - Frej, Anne; Christensen, Marvin F. (ULI development handbook series., 2001)
Packed with color photographs and illustrations, this handbook covers the best practices, techniques, and trends. It explains the development process step-by-step and includes 14 case study examples of new construction, adaptive use, airport-related development, and mixed office and industrial facilities.